KEGIATAN PENGEMBANGAN MOTORIK HALUS ANAK DI TAMAN KANAK -KANAK AISYIYAH KOTA PAYAKUMBUH - Awalul Fitri, Reno (Jurnal Ilmiah Pesona PAUD, 2015)
The background of this study shows that the development activity soft motori in kindergarten. This study belongs to descriptive research. The data was colletced througth observasion, interview, and documentation. The steps to do this research consist of: (1) data description, (2) data reduction, (3) data verification/ drawing conclusion. Kata Kunci: Kegiatan; motorik Halus